Pengaruh Kinerja Pegawai terhadap Kepuasan Masyarakat di Kantor Kecamatan Bojongsoang Kabupaten Bandung - Cepi Ardiansyah; Robbi Zidni Ilma (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to evaluate the influence of government employee performance on community satisfaction in Bojongsoang District. The performance of government employees has a crucial role in providing services to the community, and community satisfaction is the main benchmark in assessing the effectiveness of public services, this research method uses a quantitative approach with data collection techniques through questionnaires distributed to respondents who are 41 community members. in the Bojongsoang District environment. The collected data was analyzed using descriptive statistical techniques and regression with SPSS V27. to identify the relationship between government employee performance variables and community satisfaction. The research results show that the performance of government employees has a significant positive influence on community satisfaction in Bojongsoang District. Performance aspects, such as employee responsiveness, expertise, and service attitudes, have a significant contribution to the level of community satisfaction. Apart from that, external factors such as communication between the government and the community also influence the perception of community satisfaction. In conclusion, there is an influence of government employee performance on community satisfaction in Bojongsoang District. Keywords: Community Satisfaction Employee Performance; The Influence of Employee Performance on Community Satisfaction